Albanian Preschool Personnel’s Perceived Obstacles to Implementing Effective Inclusive Education - Hyseni Duraku, Zamira; Jahiu, Genta; Likaj Shllaku, Eglantina; Boci, Loreta; Shtylla, Hysnie (Frontiers in Education, 2021)
Access to high-quality early education promotes the academic success of children with disabilities; however, they are often overlooked in mainstream programs that lack essential support services. This study aimed to examine the obstacles to supporting inclusion and providing effective early education programs for children with disabilities in Albania as perceived by the preschool personnel. Preschool personnel (n = 107) working with children (three to six years old) in the municipality of Tirana, in Albania, completed the survey. The obstacles to supporting children with disabilities were identified as lack of knowledge, supportive techniques, specific working tools, suitable facilities, and support staff, insufficient cooperation with parents, and inadequate educational programs for children with disabilities. The contextual factors and practical implications of the study, as well as future directions for research, are discussed in this article.